An Ode to Gillies and Millard: "The Ten Commandments Applied to Self-Inflicted Head and Neck Gunshot Wounds". Issue 1 (March 2022) - Assi, Patrick E.; Hunzicker, Alixendra; Jones, John; Pemberton, John; Golinko, Michael Samuel
Within the field of craniofacial trauma surgery, reconstruction following high-energy ballistic injuries to the face remains a daunting task requiring a multidisciplinary approach for best outcomes. These injuries are complex with large defects requiring reconstruction of different lamellae and skeletal buttresses of the face and no 2 are exactly alike. The reconstruction efforts are multidimensional and focus on restoring facial height, width, projection, jaw occlusion, and function. We present a challenging course of a 56 year old patient with a self- inflicted gunshot wound to the face that resulted in devastating injuries to the mandible and midface. We describe our multistage and multiple technique surgical approach that spanned nearly 2 years and 11 operations that included open reduction, internal fixation of extensive facial fractures, primary bone grafting, free fibula for maxillary reconstruction and palatal fistula obliteration, pre-expanded paramedian forehead flap, and mandibular distraction. In reviewing the patient's course, his complications, and wins, we were inspired by the fundamentals principles of head and neck reconstruction as we interpreted from the famous "Ten Commandments of Drs. Gillies and Millard." We discuss these Commandments with the reader in our reflection of this challenging reconstruction and hope others, particularly, those in training are encouraged to find application of the "Ten Commandments" we review as they develop their own surgical practices and styles.